Exploring the relationship between ischemic core volume and clinical outcomes after thrombectomy or thrombolysis. (16th July 2019) - Chen, Chushuang; Parsons, Mark W.; Levi, Christopher R.; Spratt, Neil J.; Miteff, Ferdinand; Lin, Longting; Cheng, Xin; Lou, Min; Kleinig, Tim; Butcher, Kenneth; Dong, Qiang; Bivard, Andrew
Abstract : Objective: To assess whether complete reperfusion after IV thrombolysis (IVT-R) would result in similar clinical outcomes compared to complete reperfusion after endovascular thrombectomy (EVT-R) in patients with a large vessel occlusion (LVO). Methods: EVT-R patients were matched by age, clinical severity, occlusion location, and baseline perfusion lesion volume to IVT-R patients from the International Stroke Perfusion Imaging Registry (INSPIRE). Only patients with complete reperfusion on follow-up imaging were included. The excellent clinical outcome rates at day 90 on the modified Rankin Scale (mRS) were compared between EVT-R vs IVT-R patients within quintiles of increasing baseline ischemic core and penumbral volumes. Results: From INSPIRE, there were 141 EVT-R patients and 141 matched controls (IVT-R) who met the eligibility criteria. In patients with a baseline core <30 mL, EVT-R resulted in a lower odds of achieving an excellent outcome at day 90 compared to IVT-R (day 90 mRS 0–1 odds ratio 0.01, p < 0.001). The group with a baseline core <30 mL contained mostly patients with distal M1 or M2 occlusions, and good collaterals ( p = 0.01). In patients with a baseline ischemic core volume >30 mL (internal carotid artery and mostly proximal M1 occlusions), EVT-R increased the odds of patients achieving an excellent clinical outcome (day 90 mRS 0–1 odds ratio 1.61, p < 0.001) and there was increased symptomatic intracranial hemorrhage in the IVT-R group with core >30 mL (20% vs 3% in EVT-R, p = 0.008). Conclusion: From this observational cohort, LVO patients with larger baseline ischemic cores and proximal LVO, with poorer collaterals, clearly benefited from EVT-R compared to IVT-R alone. However, for distal LVO patients, with smaller ischemic cores and better collaterals, EVT-R was associated with a lower odds of favorable outcome compared to IVT-R alone.